Elevated TRIM44 promotes intrahepatic cholangiocarcinoma progression by inducing cell EMT via MAPK signaling - Rui Peng; Peng‐Fei Zhang; Chi Zhang; Xiao‐Yong Huang; Yan‐bing Ding; Bin Deng; Dou‐Sheng Bai; Ya‐Ping Xu (Cancer Medicine, 2018)
Abstract Surgical results for intrahepatic cholangiocarcinoma (ICC) remain unsatisfactory due to the high rate of recurrence. Here, we investigated that the expression and roles of tripartite motif‐containing protein 44 (TRIM44) in human ICCs. Firstly, TRIM44 expression was analyzed in several kinds of cancers by referring to public Oncomine database, and the expressions of TRIM44 mRNA and protein were tested in ICC and corresponding paratumorous tissues. Secondly, functions and mechanisms of TRIM44 in ICC cells were further evaluated by TRIM44 interference and cDNA transfection. Finally, the prognostic role of TRIM44 was assessed by Kaplan–Meier and Cox regression. We found that TRIM44 expression was upregulated in ICC tissues compared with corresponding paratumorous tissues, which were consistent with the results from the public cancer database. Knockdown of TRIM44 repressed the invasion and migration of ICC cells, while increased the ICC cell apoptosis. Additionally, high level of TRIM44 was shown to induce ICC cell epithelial to mesenchymal transition (EMT). Mechanistically, a high level of TRIM44 was found to activate MAPK signaling, and a MEK inhibitor, AZD6244, reversed cell EMT and apoptosis endowed by TRIM44 overexpression. Clinically, TRIM44 expression was positively associated with large tumor size (P = 0.035), lymphatic metastasis (P = 0.008) and poor tumor differentiation (P = 0.036). Importantly, patients in TRIM44high group had shorter overall survival and higher cumulative rate of recurrence than patients in TRIM44low group. Our results suggest elevated TRIM44 promotes ICC development by inducing cell EMT and apoptosis resistance, and TRIM44 is a valuable prognostic biomarker and promising therapeutic target of ICC.